A study on the usage of antimicrobial agents and adverse drug reaction of antimicrobial used in a tertiary care hospital in North East India - Patowary, Susmita; Lahkar, Mangala; Lihite, Ratan J. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Irrational use of antimicrobial agents (AMAs) has led to large scale development of drug resistance and adverse drug reactions (ADRs) which has become a growing world -wide concern. The study was conducted to analyze the prescribing pattern of AMAs and to evaluate the reported ADR of the AMAs prescribed. Methods: A prospective study was conducted by analyzing 900 case sheets receiving AMAs in a tertiary care hospital. The study plan included analysis of average number of AMA prescribed, morbidity profile of patients, types of AMAs used, drug prescribed by generic/brand name, injectable AMA preparations and appropriateness of indication of AMA used. Thirty reported cases of ADR were evaluated for their casualty by Narnajo’s scale and severity by Hartwigs scale. Results: Average number of drugs per prescription was 1.54. Most common morbidity was fever due to various causes. 86.2% of AMA used was antibiotics. About 72.0% of AMAs were prescribed by generic name. Percentage of injectable preparation was 85.0%. 65.0% of drugs were prescribed from Essential drug list (EDL). Most offending drug for ADR was fixed drug combination (FDC) 30.0%. Common organ system involved was skin (63.3%). Most of the ADR were possible (80.0%) and mild (76.6%) in nature. Conclusions: Average number of AMAs per prescription was1.54. Percentage of drug prescribed by generic name is encouraging. However use of injectable preparation was very high. Majority of AMAs prescribed were antibiotics which is also very high. Periodic prescription audit will provide feedback to the prescribers and help in reducing the prescribing error and ADR cases.